Pengaruh Persepsi Manfaat, Kemudahan Dan Cashback Terhadap Minat Penggunaan Go-Pay (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis angkatan 2019 di Universitas Islam Malang) - Indana Zulfah; Muhammad Ridwan Basalamah; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The telecommunications and banking sector industries continue to compete by creating various electronic money products that prioritize speed, convenience and efficiency when making transactions. Competition in various kinds of digital wallets in Indonesia certainly results in various fintech brands continuing to carry out marketing strategies, including Go-Pay.This research is to find out and analyze the perceived usefulness, ease of use and cashback on interest in using Go-Pay. The population in this study were students of the 2019 Faculty of Economics and Business, Islamic University of Malang. The sampling technique uses purposive sampling which is a sample collection technique based on certain criteria with 90 respondents. The analysis technique uses multiple linear regression analysis. The results of this study indicate that the perceived usefulness (X1), Ease of use (X2) and cashback (X3) variables contribute to the variable behavioral intention Go-Pay by 67.5% and the remaining 32.5% is explained by other independent variables that are not included in the study. And simultaneously and partially the perceived benefits, convenience and cashback have a significant effect on the intention to use Keywords: Perceived usefulness, Ease Of Use, Cashback, Behavioral intention.